Tricho-rhino-phalangeal syndrome with supernumerary teeth - Kantaputra P. (2014)
Tricho-rhino-phalangeal syndromes (TRPS) are caused by mutation or deletion of TRPS1, a gene encoding a GATA transcription factor. These disorders are characterized by abnormalities of the hair, face, and selected bones. Rare cases of individuals with TRPS displaying supernumerary teeth have been reported, but none of these has been examined molecularly. We used two different approaches to investigate a possible role of TRPS1 during tooth development. We looked at the expression of Tprs1 during mouse tooth development and analyzed the craniofacial defects of Trps1 mutant mice. In parallel, we investigated whether a 17-year-old Thai boy with clinical features of TRPS and 5 supernumerary teeth had mutation in TRPS1. We report here that Trps1 is expressed during mouse tooth development, and that an individual with TRPS with supernumerary teeth has the amino acid substitution A919V in the GATA zinc finger of TRPS1. These results suggest a role for TRPS1 in tooth morphogenesis.